(untitled) (مجلة الفاروق للعلوم, 2026)
This study explores the morphological word-formation processes and discursive functions of Generation Z and Generation Alpha slang in a spoken educational context through a guest speech delivered by content creator Xiaoma to high school students at Westtown School. Although previous studies have examined youth slang primarily in digital and social media communication, little attention has been paid to its use in face-to-face educational discourse. Using a qualitative discourse-analytic approach, the study analyzed a transcribed segment of the speech (2:10–6:50). Mattiello’s (2008) framework was used to classify the slang items according to their word-formation processes, and the students’ non-verbal responses were examined throughout the speech. Thirty-nine single-word slang items were identified and classified into seven word-formation processes. Conversion was the most frequent word-formation process, followed by suffixation, clipping, acronyms and initialisms, compounding, word manufacture, and variation. Behavioral, emotional, and cognitive engagement was evident in the students’ smiles, laughter, applause, eye contact, and head nodding during the speech. These findings highlight the value of contemporary slang in creating more engaging educational discourse and extend current understanding of youth slang beyond digital communication.